2018
DOI: 10.1007/s12250-018-0039-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C in Laos: A 7-Year Retrospective Study on 1765 Patients

Abstract: Hepatitis C virus (HCV) is a global health concern, notably in Southeast Asia, and in Laos the presentation of the HCV-induced liver disease is poorly known. Our objective was thus to describe a comprehensive HCV infection pattern in order to guide national health policies. A study on a group of 1765 patients formerly diagnosed by rapid test in health centres was conducted at the Centre of Infectiology Lao Christophe Merieux in Vientiane. The demographic information of patients, their infection status (viral l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Among the patients, 10.6% had both a high level of HBV DNA over 10,000 IU/mL and elevated aminotransferases. However, only 2.4% of them received treatment for chronic hepatitis [10,11].…”
Section: Hepatitis B Virusmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the patients, 10.6% had both a high level of HBV DNA over 10,000 IU/mL and elevated aminotransferases. However, only 2.4% of them received treatment for chronic hepatitis [10,11].…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…More recently, a retrospective study conducted on 1765 HCV-infected patients showed that, in Vientiane, 28% had high viral loads (>6log10). About 23% of patients had levels of aminotransferases indicative of liver damage >40 IU/mL, but less than 20% of them received antiviral drugs [10,11]. In Laos, circulating strains overwhelmingly belong to genotype 6 >95%, the Southeast Asian version of HCV, with frequent viral isolates specific to the local population [18][19][20].…”
Section: Hepatitis C Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…HCV infection causes acute and chronic hepatitis in humans with a high propensity for chronicity. A large number of HCV-infected patients fail to clear this virus and remain asymptomatic for years to develop severe liver diseases such as cirrhosis and hepatocellular carcinoma (Paboriboune et al 2018). The capability of establishing chronic infection by HCV is partly due to its ability to evade host innate immune responses (Horner and Gale 2013).…”
Section: Introductionmentioning
confidence: 99%